A nationwide epidemiological study of myasthenia gravis in Latvia. (8th January 2018) - Zieda, A.; Ravina, K.; Glazere, I.; Pelcere, L.; Naudina, M. S.; Liepina, L.; Kamsa, I.; Kurjane, N.; Woodhall, M.; Jacobson, L.; Leite, M. I.; Tandon, K.; et al.
Abstract : Background and purpose: Myasthenia gravis (MG) is an autoimmune disorder characterized by fatigable muscle weakness due to antibody‐mediated impairment of neuromuscular transmission. The aim of this study was to investigate the incidence and prevalence of MG in Latvia, and to characterize this population by well‐established clinical parameters such as age at onset, presence of associated antibodies and thymus pathology. Methods: All prevalent cases on 1 January 2015 and cases of patients newly presenting with MG symptoms from 1 January 2010 to 31 December 2014 were selected from the database of the Neuromuscular Disease Clinic of Pauls Stradins Clinical University Hospital and Children's Clinical University Hospital. Crude rates were calculated based on population data. These were directly age‐standardized to the European and World Health Organization world standard populations. The analysis of clinical characteristics was carried out in a cohort of patients who had undergone a complete set of electrophysiological, serological and radiological investigations ( n  = 153; 68%). Results: During the study period 99 incident and 226 prevalent cases were identified. The total crude MG incidence was 9.7 per million person‐years. The prevalence of MG on 1 January 2015 was 113.8 per million. 54.2% of patients tested positive for acetylcholine receptor antibodies, 7.8% for muscle specific kinase antibodies and 1.3% for lipoprotein related protein 4 antibodies. Conclusions: This is the first study of MG in Latvia and the second population‐based study of MG in Eastern Europe. Our epidemiological results are similar to those in some other European and Northern American countries, and show high prevalence and increasing incidence of late‐onset MG.